Citizen science data predict high potential for macrofungal refugia outside protected riparian areas. (February 2021) - Fink, Sabine; Gross, Andrin; Senn-Irlet, Beatrice; Scheidegger, Christoph
Abstract: Protected areas with restricted management can provide refugia for fungi, but are usually selected based on conservation strategies for flora and fauna. Despite the important role of fungi in floodplains, they are rarely considered in conservation projects. The SwissFungi database covering all biogeographic regions in Switzerland, and consisting of 84% citizen science data, provided a valuable basis to define fungal riparian species: 99.29% of 990 species were reported at least once from the riparian zone, while 15% of species showed a measurable riparian affinity. Species distribution modelling for 129 riparian macrofungi revealed that the predicted distribution is driven by temperature for most species. There were significantly more records per species inside compared to outside protected areas, when correcting for size differences (21% of the area in Switzerland is protected). In contrast, the model predicted significantly more suitable habitat outside currently protected areas. Unprotected areas harbor a high potential for the creation of newly protected areas for the conservation of riparian fungi. The database information and the modelling approach provided crucial information for future monitoring and conservation projects along rivers. Highlights: Definition of target fungi for conservation and restoration of riparian areas. Species distribution models with geological, topographic and climatic predictors. More relative fungal records inside protected areas. More predicted suitable habitat outside protected areas. Application for fungal conservation and restoration projects.